BIOLEACHING LOGAM TANAH JARANG DARI ABU DASAR HASIL PEMBAKARAN BATUBARA DI PLTU SURALAYA MENGGUNAKAN BAKTERI BACILLUS NITRATIREDUCENS STRAIN SKC/L-2 - Zanuar Reza, Achmad
Coal is a pledge energy source in Indonesia, especially for the power plant industry. However, the use of coal in the power plant industry causes a large environmental impact along with the production of waste in the form of fly ash (FA) and bottom ash (BA). Meanwhile, rare earth metals (REMs) is a metal group consisting of 15 elements of lanthanides, including scandium (Sc) and yttrium (Y). The everincreasing demand for REMs for various purposes has driven the work to find alternative sources of REMs. Bottom ash is one of the potential sources of REMs. On the other hand, bioleaching is an environmentally friendly technological innovation that potentially can be used to extract REMs from bottom ash. In this research, bioleaching of bottom ash from coal combustion at Suralaya Power Plant will be carried out to extract REMs with the help of the bacterium Bacillus nitratireducens strain SKC/L-2.